(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2005)
We present the magnetostratigraphy and conodont biostratigraphy across the Carnian-Norian boundary from a 70 m-thick limestone section located at Guri Zi in northern Albania. A total of 14 magnetozones were observed. The Carnian-Norian boundary is placed in a thin stratigraphic interval between the last occurrence of Paragondolella nodosa and the first occurrence of Epigondolella abneptis. Data from Guri Zi are in substantial agreement with already published data from Silicka Brezova in Slovakia and Pizzo Mondello in Sicily, which complessively indicate that the conodont Carnian-Norian boundary, when magnetostratigraphically traced onto the Newark astrochronological polarity time scale (APTS), has an age of 228-227 Ma.